POTENSI PROPOLIS TERHADAP PROGRESIVITAS ATEROSKLEROSIS PADA MODEL HEWAN HIPERKOLESTEROLEMIA: SYSTEMATIC REVIEW - Az-Zahra Fathiya Ishbir Hikmata (2022)
Hypercholesterolemia is a fat metabolism disorder characterized by elevated total cholesterol, LDL (low density lipoprotein), triglycerides, and decreased HDL (high density lipoprotein). According to Riskesdas data, men and women had a hypercholesterolemia rate of 48 percent and 54.3 percent, respectively. This lipid imbalance may act as a trigger for the development of atherosclerosis of the blood arteries. Many ways have been used in several attempts to prevent atherosclerosis, one of which is the use of propolis. In several previous studies, propolis was found to inhibit the formation of atherosclerosis. Methods: The PRISMA-P (Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols) 2015 approach was used to create a systematic review. The study discussed the effect of propolis treatment on the histological appearance of atherosclerosis progression in the selected journal. Results: Propolis has an antiatherosclerotic action by modifying lipids, stopping the inflammatory process, and slowing the LDL oxidation process, which prevents the formation of atherosclerosis, according to eight peer-reviewed articles. Conclusion: Flavonoids and propolis ethanol extract (EEP) inhibit the formation of atherosclerosis by reducing lesion thickness, lipid accumulation, total cholesterol concentration, and inflammatory reactions, thereby reducing smooth muscle cell proliferation and migration in the tunica intima of blood vessels